2019
DOI: 10.1123/japa.2018-0346
|View full text |Cite
|
Sign up to set email alerts
|

Is Exercise Prescription in Cardiac Rehabilitation Influenced by Physical Capacity or Cardiac Intervention?

Abstract: This study investigated the influence of cardiac intervention and physical capacity of individuals attending an Australian outpatient cardiac rehabilitation program on the initial exercise prescription. A total of 85 patients commencing outpatient cardiac rehabilitation at a major metropolitan hospital had their physical capacity assessed by an incremental shuttle walk test, and the initial aerobic exercise intensity and resistance training load prescribed were recorded. Physical capacity was lower in surgical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…It has recently been demonstrated that the initial exercise prescription in an Australian cardiac rehabilitation program considers patient symptoms more than measured physical capacity [11]. Additionally, it is not clear how exercise prescription is progressed over the duration of cardiac rehabilitation.…”
Section: Introductionmentioning
confidence: 99%
“…It has recently been demonstrated that the initial exercise prescription in an Australian cardiac rehabilitation program considers patient symptoms more than measured physical capacity [11]. Additionally, it is not clear how exercise prescription is progressed over the duration of cardiac rehabilitation.…”
Section: Introductionmentioning
confidence: 99%